Importância do gene WEE1 e efeitos da sua inibição na sobrevida de células-tronco tumorais do Mieloma Múltiplo - Dantas, Rebecca Silveira Santos Barbosa [UNIFESP] (2019)
Introduction: Multiple myeloma (MM) is characterized by the infiltration of tumor plasmacytes into the bone marrow (BM), synthesis and secretion of monoclonal immunoglobulins and tissue damage. The presence of cancer stem cells (CSCs) is indicated as the predominant cause of resistance to therapy and relapses in cancer, being a subject still little explored in MM. In previous studies of our group, MM cancer stem cells (MM-CSCs) were isolated based on the expression of CD138, CD34, CD19 and ALDH1 markers. After analysis of stemness gene expression by PCR array, 82% of the genes showed differential expression between MM-CSCs and tumor plasma cells in patient samples. Among them, the WEE1 gene, responsible for the repair of DNA in the G2 phase of the cell cycle, was identified as overexpressed in MM-CSCs in relation to tumor plasmacytes. Thus, our results suggest the WEE1 molecule as a possible therapeutic target to be explored in MM. Objectives: To identify the presence of possible MM-CSCs in MM cell lines; to evaluate WEE1 gene expression in these cells; and to perform functional studies to verify the effect of the inhibition of this gene on cell viability and its potential as therapeutic target. Materials and methods: MM cell lines were submitted to sorting by flow cytometry to identify MM-CSCs (CD138- / CD19 + / CD34 + / ALDH1 +) and soft agar culture to evaluate the formation of microspheres. WEE1 expression was evaluated in the cell lines by quantitative real-time PCR (qPCR). After treatment with the WEE1 inhibitor (MK-1775), with or without proteasome inhibitor (bortezomib) pretreatment, we assessed cell viability through Prestoblue functional test, and the induction of apoptosis and the cell cycle by flow cytometry. Results: We identified the presence of MM-CSCs (CD138- / CD34 + / ALDH1 +, CD19 negative in four wild-type MM lines), and the formation of microspheres in soft agar using RPMI-8226, U266 and SKO-007. All MM cell lines showed WEE1 expression by qPCR. RPMI-8226 and U266 showed a 50% reduction in cell viability after 24 hours of incubation with MK-1775, at concentrations of 5μM and 20μM, respectively. SKO-007 showed dose and time dependence to this drug. Combination therapy with bortezomib and MK-1775 abolished the formation of soft agar microspheres in the RPMI-8226 cell line (also responsive to the use of both drugs) and U266, but SKO-007 was resistant to all drugs, isolated and combined. Treatment of bortezomib followed by MK-1775 (sequential treatment) versus bortezomib alone showed statistically significant impact on cell lines total apoptosis: 88.8% vs 74.1% in RPMI-8222; 92.5% vs 86.6% in U266; and 60.2% 30.9% on SKO-007 (p<0.05) Conclusion: The sequential combination of bortezomib and WEE1 inhibitor, MK-1775, induced apoptosis in RPMI-8226, U266, and especially SKO-007 cell lines, more efficiently than the use of the isolated drugs, highlighting its effect in inhibition of proliferation of tumor cells in MM cell lines and, potentially, in MM-CSCs.